KEPEMILIKAN INSTITUSIONAL TERHADAP PENGHINDARAN PAJAK - Afrika, Rizki (Universitas Muhammadiyah Palembang, 2021)
The purpose of this research is to analyze the effect of Institutional Ownership on Tax Avoidance with 5 control variables, which are Profitability, Leverage , Company Size, Sales growth and Fixed Asset Intensity. This research uses quantitative approach with secondary data obtained from financial reports published on the IDX website in 2016-2019. The population of this research is manufacturing companies in the Mining sector and Basic Industry and Chemicals . The sample selection method used is purposive sampling with 43 sample companies. The results of the research prove that Institutional Ownership has a negative effect on Tax Avoidance